Synthesis of Bis‐(2‐thiazolyl)amine Analogues and Evaluation of Their Antibacterial, Antioxidant and Cytotoxic Activities. Issue 40 (5th November 2019) - Alaraidh, Ibrahim A.; Okla, Mohammad K.; Alamri, Saudi A.; AL‐ghamdi, Abdullah A.; Soufan, Walid H.; Allam, Ahmed A.; Fouda, Moustafa M. G.; Gaffer, Hatem E.
Abstract: An effective and economical preparation of bis ‐(2‐thiazolyl)amine analogues was achieved by the reaction of 3‐(5‐arylazothiazol‐2‐yl)thioureas with various halogenated carbonyl reagents (namely; chloroacetic acid, diethyl bromomalonate, chloroacetone and phenacyl bromide). The physical and spectral analyses were performed to demonstrate the correct configurations of all incorporated analogues. It is clear that most of synthesized bis ‐(2‐thiazolyl)amine derivatives revealed good biological efficacy, including anticancer, antibacterial and antioxidant. The synthesized bis ‐(2‐thiazolyl)amine derivatives were investigated as cytotoxic agents against four different cell lines, in which the results revealed potent efficacies of the synthesized derivatives relative to the results of antibiotic standards. In addition, the antioxidant efficacy of all analogues was determined using ABTS + "2, 2′‐azino‐bis(3‐ethylbenzothiazoline‐6‐sulphonic acid" method. Abstract : A new strategy was developed to prepare bis ‐(2‐thiazolyl)amine analogues in a few stages. Reasonable results were demonstrated for the preps analogues toward yeasts and fungal strains beside their antimicrobial, antioxidant and cytotoxic activities.